BRS Clara raisins production: Effect of the pre-treatment and the drying process on the phenolic composition - Olivati, Carolina [UNESP]; Nishiyama, Yara P.O. [UNESP]; Silva, Roberto da [UNESP]; Gómez-Alonso, Sergio; Lago-Vanzela, Ellen S. [UNESP] (Elsevier, 2022)
The present study aimed to evaluate how the drying process, using extra virgin olive oil (EVOO) as a pre-treatment to accelerate the drying process of the grapes, influenced the qualitative and quantitative profile of phenolic compounds (PC). The effect of the harvest and the treatment (fresh grapes, raisins without and with EVOO) on the phenolic profile, as well as the interaction of these two factors, were also evaluated. The results showed that the phenolic profile was not just influenced by the harvest, but also by the treatment. For the raisins obtained with EVOO, the total mean content of stilbenes, flavonols, hydroxycinnamic acid derivatives, proanthocyanidins, and flavan-3-ols were equal to or greater than those obtained for the raisins without pre-treatment. These results along with an average reduction of 39.3 % ± 5.5 % in the drying time promoted by the EVOO pre-treatment, led us to conclude that such pre-treatment was beneficial during the dehydration process for most PC classes investigated.
Keywords: Dried grapes; Extra virgin olive oil; HPLC-DAD-ESI-MSn; Hybrid grape cultivar, BRS Clara; Phenolic composition